Exploration of Fort Marlborough Bengkulu and Its Implications for Mathematics Learning in School - Zamzaili, Zamzaili; Riyani, Rizki; Haji, Saleh (FKIP Universitas Lampung, 2022)
This study aims to describe the facts, concepts, principles, and mathematical operations contained in the ethnomathematics of Fort Marlborough Bengkulu. This research is qualitative research with an ethnographic approach. The subjects in this study were seven: one Bengkulu history expert, two Marlborough Fort synthesizers, two mathematicians, and two Bengkulu City mathematics teachers. Data were collected through observation, interviews, and documentation. The data were analyzed through three stages, data reduction, data presentation, and conclusion. The results of the research found include, there are mathematical facts on the ethnomathematics of the Marlborough fort Bengkulu, Facts in the form of points, wake-up webs, lines, and line segments. Concepts: flat build, space build, trigonometry on the building and courtyard of Fort Marlborough. Principles: area and perimeter of plane figures, quadratic functions, volumes and surface areas of figures, trigonometric ratios: Keywords: ethnomathematics, ethnographic research, Fort Marlborough DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1471-1480